Engaging Nurses in Professional Governance Across a Hospital Service Line - Lee, Mark; Pappas, Sharon; Yolo, Ron (Nurse leader, 2025)
Strong professional governance is linked with higher levels of nurse engagement and lower levels of nurse turnover. Nevertheless, a large academic medical center found that professional governance engagement declined after the pandemic. A quality improvement project utilizing the Plan-Do-Study-Act methodology was developed to innovate professional governance, developing and implementing a service line council across eight medical–surgical units of a hospital service line sharing greater clinical, administrative, and educational resources than before. Over 3 months, the project indicated a statistically significant difference in the mean work empowerment scores of clinical nurses participating postsurvey (23.29 out of 30), compared to presurvey (19.75), t = 3.62, df = 31.8, p = .001. The results demonstrate the importance of aligning professional governance with evolving clinical and administrative structures for patients and the profession.